Multihazard Response Control of Base-Isolated Buildings under Bidirectional Dynamic Excitation - Daniel H. Zelleke; Sandip K. Saha; Vasant A. Matsagar (Shock and Vibration)
The issues of safety and posthazard functionality of structures under multihazard scenarios are some of the significant challenges in the current dynamic and rapidly growing urban environment. In this paper, multistory base-isolated buildings are investigated under the independent multihazard scenario of earthquake and blast-induced ground motion (BIGM). Multistory building models equipped with five different types of isolation systems, namely, the laminated rubber bearing (LRB), lead-rubber bearing (N-Z system), pure friction (PF) system, friction pendulum system (FPS), and resilient-friction base isolator (R-FBI) are assessed under bidirectional multihazard excitations. The suitability of the isolation systems and their key parameters in protecting multistory buildings is evaluated. Furthermore, the influence of the superstructure characteristics, such as the superstructure damping and the number of stories, is also assessed. The effect of bidirectional hazards on fixed-base buildings is also presented for comparison. The key response quantities of base-isolated buildings are presented and compared for different isolation systems. Parametric investigations are also conducted, and the trends of the response quantities are presented to study the influence of important parameters of isolation systems in protecting the buildings under the multihazard scenario of earthquake and BIGM. The results of the investigation show that the behaviors of the buildings equipped with various isolation systems are different for the two hazards. Moreover, the influences of the key parameters of the isolation systems are found to be different for various hazards. Therefore, the selection of design parameters of isolation systems shall be made with due consideration of the influence of multiple hazards. Additionally, the influence of the properties of the superstructure, such as the number of stories and the damping of the superstructure, on the behavior of the base-isolated buildings under the multihazard loading, is presented.